Comic media development to improve students' understanding of comparative concepts - Sartika, Dian; Widadah, Soffil; Ayuningtyas, Nurina (Universitas Islam Negeri Raden Intan Lampung, 2022)
Understanding mathematical material begins with reading, but there are still many students who need reading interest so that it will affect their ability to deal with problems. It is also important to learn mathematics using mathematics learning media. This will motivate students to read the material provided so that students can easily understand it. The purpose of this study is to explain the process and results of developing comics media for comparative material. The development of comic media on this comparison material is to improve students' understanding of the concept of comparison. The quality of this media development is seen from the aspects of validity, effectiveness, and practicality. This research is development research using five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. This research produces a mathematical comic comparison material. The results are: (1) based on the comic media quality assessment for experts, the average score is 4.28 and is included in the very valid classification, (2) based on the results of student learning tests, the media created is declared effective by solving test questions 95% with an average class score of 84.5 and included in the very effective classification, (3) based on the student response questionnaire, the comics media made were declared practical with a total average percentage of 97.2% which were included in the very practical classification. Thus the developed comics media can be used for learning mathematics comparative material.